Evaluation of mature cow weight: Genetic correlations with traits used in selection indices, correlated responses, and genetic trends in Nelore cattle - Boligon, A. A. [UNESP]; Carvalheiro, R.; Albuquerque, L. G. [UNESP] (Oxford University Press (OUP), 2013)
Genetic correlations of selection indices and the traits considered in these indices with mature weight (MW) of Nelore females and correlated responses were estimated to determine whether current selection practices will result in an undesired correlated response in MW. Genetic trends for weaning and yearling indices and MW were also estimated. Data from 612,244 Nelore animals born between 1984 and 2010, belonging to different beef cattle evaluation programs from Brazil and Paraguay, were used. The following traits were studied: weaning conformation (WC), weaning precocity (WP), weaning muscling (WM), yearling conformation (YC), yearling precocity (YP), yearling muscling (YM), weaning and yearling indices, BW gain from birth to weaning (BWG), postweaning BW gain (PWG), scrotal circumference (SC), and MW. The variance and covariance components were estimated by Bayesian inference in a multitrait analysis, including all traits in the same analysis, using a nonlinear (threshold) animal model for visual scores and a linear animal model for the other traits. The mean direct heritabilities were 0.21 ± 0.007 (WC), 0.22 ± 0.007 (WP), 0.20 ± 0.007 (WM), 0.43 ± 0.005 (YC), 0.40 ± 0.005 (YP), 0.40 ± 0.005 (YM), 0.17 ± 0.003 (BWG), 0.21 ± 0.004 (PWG), 0.32 ± 0.001 (SC), and 0.44 ± 0.018 (MW). The genetic correlations between MW and weaning and yearling indices were positive and of medium magnitude (0.30 ± 0.01 and 0.31 ± 0.01, respectively). The genetic changes in weaning index, yearling index, and MW, expressed as units of genetic SD per year, were 0.26, 0.27, and 0.01, respectively. The genetic trend for MW was nonsignificant, suggesting no negative correlated response. The selection practice based on the use of sires with high final index giving preference for those better ranked for yearling precocity and muscling than for conformation generates only a minimal correlated response in MW. © 2013 American Society of Animal Science. All rights reserved.
Keywords: Bayesian inference; Beef cattle; Body weight gain; Scrotal circumference; Visual scores; aging; animal; cattle; female; genetic selection; genetics; growth, development and aging; male; Aging; Animals; Cattle; Female; Male; Selection, Genetic